2013
DOI: 10.1159/000356194
|View full text |Cite
|
Sign up to set email alerts
|

Sonorant Onset Pitch as a Perceptual Cue of Lexical Tones in Mandarin

Abstract: Lexical tone identification requires a number of secondary cues, when main tonal contours are unavailable. In this article, we examine Mandarin native speakers' ability to identify lexical tones by extracting tonal information from sonorant onset pitch (onset contours) on syllable-initial nasals ranging from 50to 70 ms in duration. In experiments I and II we test speakers' ability to identify lexical tones in a second syllable with and without onset contours in isolation (experiment I) and in a sentential cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The results from Brenner's studies indicate that recognizing tones in casual speech is more difficult than in careful speech. He also shows that tone perception in casual speech is a complex interaction of acoustic cues and not just based on pitch, which is in line with previous careful speech research (e.g., Taft & Chen, 1999;Fu and Zeng, 2000;Liu and Samuel, 2004;Chen & Tucker, 2013). Brenner's results suggest that in everyday conversations, listeners may rely on different cues for language processing than would be expected based on laboratory studies alone.…”
Section: Differences In Tones and Intonationsupporting
confidence: 83%
“…The results from Brenner's studies indicate that recognizing tones in casual speech is more difficult than in careful speech. He also shows that tone perception in casual speech is a complex interaction of acoustic cues and not just based on pitch, which is in line with previous careful speech research (e.g., Taft & Chen, 1999;Fu and Zeng, 2000;Liu and Samuel, 2004;Chen & Tucker, 2013). Brenner's results suggest that in everyday conversations, listeners may rely on different cues for language processing than would be expected based on laboratory studies alone.…”
Section: Differences In Tones and Intonationsupporting
confidence: 83%
“…P 2 through P 4 were always vowels. Since it has been shown that sonorant onset consonants can signal tonal information (Chen & Tucker, 2013; Howie, 1974), the nasals /m/ and /n/ and the glides and liquids /l/, /ʐ/, and /tɕ/ ([m], [n], [l], [r], and [j] in Pinyin) were allowed to carry tone, in addition to the subsequent vowels. This was done by setting T HS-1 to a tone unit if P 1 corresponded to a vowel or sonorant consonant; otherwise, T HS-1 was set to the “silent” tone unit (T silent ).…”
Section: How the Trace-t Model Workmentioning
confidence: 99%
“…However, regarding the low-falling tone differentiation, the tone shapes are absolutely contrasting; the low tone is a static tone while the falling tone is a contour tone. This could lead to the interpretation that the perception cue lies in the pitch heightand not the shape of the tone, as reported in a number of previous research (Chen& Tucker, 2013;Tong et al, 2014). The low tone pitch height is at a low level, similar to that of the falling tone.…”
Section: Discussionmentioning
confidence: 74%